2005
DOI: 10.3346/jkms.2005.20.4.618
|View full text |Cite
|
Sign up to set email alerts
|

Bi-weekly Chemotherapy of Paclitaxel and Cisplatin in Patients with Metastatic or Recurrent Esophageal Cancer

Abstract: Although various combinations of chemotherapy regimens have been tried for patients with esophageal cancer, their duration of survival is extremely poor. In this study, we investigated the safety and clinical efficacy of paclitaxel and cisplatin chemotherapy in metastatic or recurrent esophageal cancer. 32 patients enrolled in this study and the median age was 60 yr. Of all the 32, 28 patients (88%) had been treated previously, 22 of them with chemotherapy or radiation therapy. All patients in the study receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Similar results were seen in a study by Ilson et al (RR 44%) and Polee et al (43%) with the same combination in advanced esophageal cancer as first line combination chemotherapy [43,44]. In a study by Cho et al 28 patients out of 32 (88%) had already been treated previously before they received biweekly paclitaxel (90 mg=m 2 ) followed by cisplatin (50 mg=m 2 ) [45]. The objective response rate was 41% with a median overall survival of 7 months.…”
Section: Combinations With Taxanessupporting
confidence: 81%
“…Similar results were seen in a study by Ilson et al (RR 44%) and Polee et al (43%) with the same combination in advanced esophageal cancer as first line combination chemotherapy [43,44]. In a study by Cho et al 28 patients out of 32 (88%) had already been treated previously before they received biweekly paclitaxel (90 mg=m 2 ) followed by cisplatin (50 mg=m 2 ) [45]. The objective response rate was 41% with a median overall survival of 7 months.…”
Section: Combinations With Taxanessupporting
confidence: 81%
“…Previous studies showed response rates of 12.5%-44.2% and median survival periods of 6-10.4 months. On the other hand, the median survival period of patients with ESCC for whom rst-line therapy failed is only 3 to 6 months if they do not receive chemotherapy (14)(15)(16)(17)(18)(19). Despite the fact that rst-line therapy in our patient with ESCC failed, we were able to control liver metastasis and lymph node metastases because of the high dose of PBT and the biological effective advantage of PBT compared to conventional X-ray therapy.…”
Section: Discussionmentioning
confidence: 99%